A Novel Aluminum‐Ion Battery: Al/AlCl3‐[EMIm]Cl/Ni3S2@Graphene. Issue 13 (27th April 2016) - Wang, Shuai; Yu, Zhijing; Tu, Jiguo; Wang, Junxiang; Tian, Donghua; Liu, Yingjun; Jiao, Shuqiang
Abstract : Due to an ever‐increasing demand for electronic devices, rechargeable batteries are attractive for energy storage systems. A novel rechargeable aluminum‐ion battery based on Al 3+ intercalation and deintercalation is fabricated with Ni3 S2 /graphene microflakes composite as cathode material and high‐purity Al foil as anode. This kind of aluminum‐ion battery comprises of an electrolyte containing AlCl3 in an ionic liquid of 1‐ethyl‐3‐methylimidazolium chloride ([EMIm]Cl). Galvanostatic charge/discharge measurements have been performed in a voltage range of 0.1–2.0 V versus Al/AlCl4 − . An initial discharge specific capacity of 350 mA h g −1 at a current density of 100 mA g −1 is achieved, and the discharge capacity remains over 60 mA h g −1 and coulombic efficiency of 99% after 100 cycles. Typically, for the current density at 200 mA g −1, the initial charge and discharge capacities are 300 and 235 mA h g −1, respectively. More importantly, it should be emphasized that the battery has a high discharge voltage plateau (≈1.0 V vs Al/AlCl4 − ). These meaningful results represent a significant step forward in the development of aluminum‐ion batteries. Abstract : A novel rechargeable aluminium‐ion battery based on Al 3+ intercalation and deintercalation is fabricated with Ni3 S2 /graphene micro‐flakes composite as cathode materials and high‐purity Al foil as anode. It is clear that two batteries in series can light the red light‐emitting diode (LED) lamp, and the discharge capacity remains over 60 mA h g −1 and coulombic efficiency of 99% after 100 cycles.